2017
DOI: 10.1016/j.canlet.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

CTGF promotes osteosarcoma angiogenesis by regulating miR-543/angiopoietin 2 signaling

Abstract: Osteosarcoma is the most common primary solid tumor of bone. It has a high metastatic potential and occurs predominantly in adolescents and young adults. Angiopoietin 2 (Angpt2) is a key regulator in tumor angiogenesis, facilitating tumor growth and metastasis. Connective tissue growth factor (CTGF, also known as CCN2), is a cysteine-rich protein that has been reported to promote metastasis of osteosarcoma. However, the effect of CTGF on Angpt2 regulation and angiogenesis in human osteosarcoma remains largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 39 publications
4
63
0
1
Order By: Relevance
“…The occurrence and development of malignant osteosarcoma are driven by genetic effects and pathological alterations. Angiogenesis is involved in osteosarcoma proliferation, migration, invasion, metastasis and accumulating evidence shows that angiogenesis inhibition may be used as a strategy for treating osteosarcoma . Multiple angiogenesis inhibitors, such as sorafenib, sunitinib and cediranib, have been used to treat advanced osteosarcoma .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence and development of malignant osteosarcoma are driven by genetic effects and pathological alterations. Angiogenesis is involved in osteosarcoma proliferation, migration, invasion, metastasis and accumulating evidence shows that angiogenesis inhibition may be used as a strategy for treating osteosarcoma . Multiple angiogenesis inhibitors, such as sorafenib, sunitinib and cediranib, have been used to treat advanced osteosarcoma .…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis is involved in osteosarcoma proliferation, migration, invasion, metastasis and accumulating evidence shows that angiogenesis inhibition may be used as a strategy for treating osteosarcoma. 9,10 Multiple angiogenesis inhibitors, such as sorafenib, sunitinib and cediranib, have been used to treat advanced osteosarcoma. 11 However, the results of recent studies support the idea that angiogenesis inhibitors can elicit tumor adaptation and disease progression, resulting in the development of tumors with high invasive and metastatic potential.…”
Section: Introductionmentioning
confidence: 99%
“…CCN2 regulates the vascular endothelium through the production of endothelial basement membrane components and is considered as an essential mediator of vascular remodeling by regulating endothelial‐pericyte interactions . The overexpression of CCN2 in osteosarcoma cells induces angiogenesis both in vitro and in vivo through the increased production of angiopiotin‐2 . Vascular endothelial growth factor, another angiogenic factor known to be increased in BD, can directly induce CCN2 gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, accumulating evidence indicates that miR‐543 has a variety of functional roles. It was shown that endogenous miR‐543 expression was negatively regulated by connective tissue growth factor, making miR‐543 a therapeutic target in osteosarcoma metastasis and angiogenesis . Also, miR‐543 mimics was shown to promote the invasion and migration of non‐small–cell lung cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, the aim of the study is to determine the roles of miR‐543 in osteoporosis. MiR‐543 has been demonstrated to regulate a number of diseases, including osteosarcoma, lung cancer, gastric cancer, and renal cancer . More importantly, miR‐543 was shown to be associated with a number of aging‐related diseases .…”
Section: Introductionmentioning
confidence: 99%